If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(-6 + x) = 76 + -2x (-6 * 6 + x * 6) = 76 + -2x (-36 + 6x) = 76 + -2x Solving -36 + 6x = 76 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -36 + 6x + 2x = 76 + -2x + 2x Combine like terms: 6x + 2x = 8x -36 + 8x = 76 + -2x + 2x Combine like terms: -2x + 2x = 0 -36 + 8x = 76 + 0 -36 + 8x = 76 Add '36' to each side of the equation. -36 + 36 + 8x = 76 + 36 Combine like terms: -36 + 36 = 0 0 + 8x = 76 + 36 8x = 76 + 36 Combine like terms: 76 + 36 = 112 8x = 112 Divide each side by '8'. x = 14 Simplifying x = 14
| 1/3y+1/4=5/12 | | 17.12/8=x | | 5(b+1)-(b+2/2)=3 | | 5(b+1)-(b+2/2)=3 | | y=6/5(-17.5)-6 | | ln(2x^2+3x-9)=2+ln(2x^2-7x+6) | | 46.12-29=17.12/8 | | -4x+2y=7 | | 2[2+3(y-1)]=2 | | r+7(-3r+5)=95 | | 6/5x-6=2x+8 | | 0=-b-b | | (46.12-29)17.12/8=x | | 3x-9=7.5+3 | | -120=4(6x+6) | | 0=-n+4n | | 2p^2=-17p-21 | | n-6+6n=1 | | -126=9(-4+n) | | -5x+x=16 | | 21x^2=4x+1 | | 3.7-(8,1x+5,4)-(2,6x+8,3)=-3,1x+(8-1,6x) | | -4=x/2-1 | | 1/3x=-8 | | 6=4r+2r | | -5n-3n=16 | | -(3y+2)-(-2y-5)=-3 | | 3a-7=2a+2 | | 7x-6+x=3x+5 | | -12=-3x-x | | 6x+10-8x=14 | | 46.12-29=x/8 |